Azimuthal sound source localization of various sound stimuli under different conditions - Risoud, M.; Hanson, J.-N.; Gauvrit, F.; Renard, C.; Bonne, N.-X.; Vincent, C. (European annals of otorhinolaryngology, head and neck diseases, 2020)
To evaluate azimuthal sound-source localization performance under different conditions, with a view to optimizing a routine sound localization protocol. Two groups of healthy, normal-hearing subjects were tested identically, except that one had to keep their head still while the other was allowed to turn it. Sound localization was tested without and then with a right ear plug (acute auditory asymmetry) for each of the following sound stimuli: pulsed narrow-band centered on 250Hz, continuous narrowband centered on 2000Hz, 4000Hz and 8000Hz, continuous 4000Hz warble, pulsed white noise, and word (“lac” (lake)). Root mean square error was used to calculate sound-source localization accuracy. With fixed head, localization was significantly disturbed by the earplug for all stimuli (P<0.05). The most discriminating stimulus was continuous 4000Hz narrow-band: area under the ROC curve (AUC), 0.99 [95% CI, 0.95–1.01] for screening and 0.85 [0.82–0.89] for diagnosis. With mobile head, localization was significantly better than with fixed head for 4000 and 8000Hz stimuli (P<0.05). The most discriminating stimulus was continuous 2000Hz narrow-band: AUC, 0.90 [0.83–0.97] for screening and 0.75 [0.71–0.79] for diagnosis. In both conditions, pulsed noise (250Hz narrow-band, white noise or word) was less difficult to localize than continuous noise. The test was more sensitive with the head immobile. Continuous narrow-band stimulation centered on 4000Hz most effectively explored interaural level difference. Pulsed narrow-band stimulation centered on 250Hz most effectively explored interaural time difference. Testing with mobile head, closer to real-life conditions, was most effective with continuous narrow-band stimulation centered on 2000Hz.